A123 PERINATAL FACTORS AND RISK OF INFLAMMATORY BOWEL DISEASE IN THE OFFSPRING: A SYSTEMATIC REVIEW AND META-ANALYSIS. (1st March 2018) - Gentilcore, F; Chartier, M; Rousseau, M; Girard, S; Wei, S; benedetti, A; Nuyt, A; Jantchou, P
Abstract: Background: It has been hypothesized that exposure to environmental factors during critical windows of immune maturation may interfere with the immune system development and influence the subsequent risk for inflammatory bowel disease (IBD). Aims: To summarize the available data of the literature and perform a meta-analysis regarding the association between perinatal factors and the subsequent risk for Crohn's disease (CD) or ulcerative colitis (UC) in the offspring. Methods: We systematically searched the following electronic databases: Embase, PubMed, Medline, EBM Reviews to identify observational studies on the association between perinatal factors and IBD in the offspring up to April 2017. A meta-analysis was performed using RevMan 5 to obtain a combined effect measure and the 95% CI with random effects models. Pooled adjusted odds ratios (OR) with 95% confident intervals were calculated by combining the inverse of their variance for each factor. Results: Twelve studies (5 cohort studies and 7 case-control studies) were identified out of 1852 studies reviewed. Maternal diabetes during pregnancy was associated with an increased risk for CD [OR(95% CI): 1.67 (1.18–2.36 )] but not UC. Maternal age >35 years was associated with an increased risk for CD [1.65 (1.02–2.66)] but a decrease risk for UC [0.92 (0.86–0.98)]. The following perinatal factors were not associated with the risk for IBD: maternal infection, pre-eclampsia, birth weight, preterm, and low APGAR score. (See Table 1.) Conclusions: This meta-analysis suggests opposite associations between advanced maternal age and risk for CD or UC. In addition, diabetes during pregnancy appears to be associated with an increased risk for CD in the offspring. Funding Agencies: None